2020
DOI: 10.2147/ijn.s263238
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Applications of Carbon Nanotubes in the Diagnosis and Treatment of Lung Cancer: A Critical Review</p>

Abstract: The importance of timely diagnosis and the complete treatment of lung cancer for many people with this deadly disease daily increases due to its high mortality. Diagnosis and treatment with helping the nanoparticles are useful, although they have reasonable harms. This article points out that the side effects of using carbon nanotube (CNT) in this disease treatment process such as inflammation, fibrosis, and carcinogenesis are very problematic. Toxicity can reduce to some extent using the techniques such as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 115 publications
0
18
0
1
Order By: Relevance
“…Sheikhpour et al [ 273 ] critically overviewed applications of CNTs in the diagnosis and treatment of lung cancer, emphasizing that their side effects manifested during therapy such as inflammation, fibrosis, and carcinogenesis can be partially reduced by functionalization of CNTs to proper dimensions, such as a longer length, a greater width, and a greater curvature. At studying the effect of MWCNTs on the toxicity of cytotoxic compounds in macrophage (RAW 264.7), lung epithelial (A549), and breast cancer (MCF-7) cell lines, it was found that hydrophilicity/lipophilicity of the compounds was determinant.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Sheikhpour et al [ 273 ] critically overviewed applications of CNTs in the diagnosis and treatment of lung cancer, emphasizing that their side effects manifested during therapy such as inflammation, fibrosis, and carcinogenesis can be partially reduced by functionalization of CNTs to proper dimensions, such as a longer length, a greater width, and a greater curvature. At studying the effect of MWCNTs on the toxicity of cytotoxic compounds in macrophage (RAW 264.7), lung epithelial (A549), and breast cancer (MCF-7) cell lines, it was found that hydrophilicity/lipophilicity of the compounds was determinant.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Besides, quantum dots, gold, and magnetic nanoparticles were a series of nanomaterials that could be utilized to detect cancers [108]. The methods of chemotherapy, radiation therapy, and various medications are used for the detection of different cancers (for example, lung cancer [109]). These methods were not highly effective due to the non-targeted and damaging of healthy tissues such as hair follicles.…”
Section: Carbon Nanotubes Based Biosensorsmentioning
confidence: 99%
“…The theranostics activity of these carbon-based NPs is discussed later in a separate section. CNTs are the nanodevice used for the detection of cancer biomarkers [ 87 ]. These are carbon cylinders having benzene rings arranged in a regular fashion [ 88 ].…”
Section: Cancer Nanotechnology: Contemporary Research In Diagnosismentioning
confidence: 99%